2020
DOI: 10.2478/phr-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screening as a Predictor of Injury in Highly Trained Female’s Martial Arts Athletes

Abstract: Objective. This research examines the emerging role of FMS™ in the context of predicting lower extremity injury in females University athletes. The secondary purpose of this study is to investigate the differences between FMS performance comparisons between three martial arts sports to establish baseline comparisons. Method. Forty-seven university female athletes were recruited for this study, The data collected was separated into three groups based on their sports discipline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Due to the difference in technology and sports methods, the way and degree of participation of the "waist" muscle groups in sports activities also have their characteristics and present their characteristics. 10 Martial arts routine is a relatively complex, comprehensive sport. It requires more muscle group strength, collective participation, and coordinated movements to achieve its goals.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difference in technology and sports methods, the way and degree of participation of the "waist" muscle groups in sports activities also have their characteristics and present their characteristics. 10 Martial arts routine is a relatively complex, comprehensive sport. It requires more muscle group strength, collective participation, and coordinated movements to achieve its goals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Detanico, et al (2012) found that VLAn was negatively correlated with peak lactate concentration after each fight. The ability to sustain predominantly aerobic metabolism during exercise can result in lower lactate accumulation, thus decreasing the demand for glycolysis and subsequently less energy required during recovery to remove lactate and H+ from the muscle [45,53,55]. Endurance training and high-intensity interval training can increase the rate of lactate removal during intense exercise by increasing the amount of lactate transporters and mitochondrial volume, thus decreasing lactate concentration in blood [9,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Only 30-45% of them are engaged in regular exercise, and the rest are no or irregular physical activities (Eggermont et Scherder 2006) . In fact, as long as regular exercise habits are maintained, no matter the age, one can maintain a healthy body through exercise training (Swift et al 2018;yassin zenati, belkadi, et benbernou 2021), or can strengthen the function of muscles and joints, enhance balance ability, and at the same time have the effect of preventing diseases (Hess et Woollacott 2005). There are many national studies on improving physical fitness and cardiovascular disease (Almahmeed et al 2012;Belahsen et Rguibi 2006;Houti et al 2016;Nejjari et al 2013), but for middle-aged and elderly people, exercise During intervention, the safety, individuality, regularity and effectiveness of training must be given priority to achieve the benefits of sports training (Mohammed et al 2018;Taylor et al 2004;Yung et al 2009).…”
Section: Introductionmentioning
confidence: 99%